Geomatics technologies applicated for landuse on easter island (Chile) - Víctor Fernando Herrera González (Ingeniare. Revista Chilena de Ingeniería, 2007)
This project resorts al use integrated and satellite images application with high spatial resolution (QuickBirdII). Thepurpose of this project is to demonstrate the contribution of geomatics technologies for cadastral applications in EasterIsland (Chile). This project resorts use integrating satellite images with high spatial resolution (QuickBridII), GPSequipment and geographic information system (GIS) in a very particular zone in land use administration like RapaNui or Easter Island. The result obtained with high accuracy measurements, resolved the geo reference for the landuse map of the city and also defined the geometric control point for the satellite image correction process. Finally, withthe creation of this cartographic data base we can mix the information with the cartographic mosaic necessary for theMinistry of National Assets. The data gathered with this technique is very important for the government actions regardingfuture transference of land to the descendants of ancient inhabitants of the island. Also, there is special relevance in theapplication of geomatics technologies in the island, when it comes to improve the urban growth planning and peopleslife conditions